2021
DOI: 10.30935/ojcmt/11114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Utilitarian and Hedonic Value in Predicting Use of Location-Based Anonymous Social Networking Sites

Abstract: Recent years have seen a rapid rise in the popularity of location-based anonymous social networking sites (LB-ASNS). Although anonymity and site specificity have been reported to be the major attractions of these platforms, there exists a severe paucity of studies that have investigated the adoption behavior of LB-ASNS using the Technology Acceptance Model as the primary theoretical framework. The goal of this study is to utilize an extended version of TAM to explain the actual use of LB-ASNS. We demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…The main theory of this research is the Technology Acceptance Model (TAM) [25], TAM theory, the user's intention in using the system is related to 3 factors, namely PU, PEU, and ATU (attitude toward using). Furthermore, Mathieson [25] concluded that the three variables are the main determinants of whether the user will refuse or accept using the system [26]. A strong correlation between behavioral intention and perceived usefulness will determine the intention of using the system.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…The main theory of this research is the Technology Acceptance Model (TAM) [25], TAM theory, the user's intention in using the system is related to 3 factors, namely PU, PEU, and ATU (attitude toward using). Furthermore, Mathieson [25] concluded that the three variables are the main determinants of whether the user will refuse or accept using the system [26]. A strong correlation between behavioral intention and perceived usefulness will determine the intention of using the system.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…The main vector of the research presented here is aimed to predict the real behaviour of a person through the features of his virtual activity in social networks (Hiranyachattada & Kusirirat, 2020;Khandelwal, & Gotlieb, 2021;Levina et al, 2019;Minakhmetova et al, 2017;Orekhovskaya et al, 2019;Owan et al, 2020;Piralova et al, 2020;Razumovskaya et al, 2018;Rubio et al, 2020;Yusupov, 2019). The markers are the metrics of the personal profile of a social network's user.…”
Section: Introductionmentioning
confidence: 99%